A Novel Analytical Method for Trace Ammonium in Freshwater and Seawater Using 4-Methoxyphthalaldehyde as Fluorescent Reagent. (1st September 2015) - Liang, Ying; Pan, Yingming; Guo, Qing; Hu, Hongzhi; Wu, Chancui; Zhang, Qian
Abstract : A novel fluorescent reagent for determination of ammonium, 4-methoxyphthalaldehyde (MOPA), was successfully synthesized in this study. Under alkaline conditions, MOPA could reacted with ammonium rapidly at room temperature, producing fluorescent substance which had maximum excitation at 370 nm and emission wavelength at 454 nm. Based on this, a novel fluorescence analysis method was established for the determination of trace ammonium in natural water. Experimental parameters including reagent concentration, pH, reaction equilibrium time, and metal ions masking agent were optimized. The results showed that the optimized MOPA concentration was 0.12 g/L, pH was in the range of 11.2–12.0, and sulfite concentration was 0.051 g/L, respectively. Metal ions masking agent had no obvious effect on the fluorescence signal. With the reaction time of 15 minutes, linear range of this method was between 0.025 and 0.300  μ mol/L, and the method detecting limit was 0.0058  μ mol/L. The matrix recovery of the proposed method was in the range of 93.6–108.1%. Compared with the OPA method, this method was much more sensitive and rapid without the interference of background peak and would be more suitable for developing a portable fluorescence detection system.